Asset Management Moderates Liquidity Against Non-Performing Loans - Wulandari, Ika; Sri Utami, Endang (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This study was conducted with the aim of knowing the influence of liquidity proxied with Loan to Deposit Ratio (LDR) on Non-Performing Loans proxied with Non Performing Loans (NPL). In addition, research was also conducted to determine the ability of asset management to moderate liquidity against problem loans. This type of research is quantitative research using secondary data. The study was conducted on Rural Banks in Indonesia. Samples were taken by purposive sampling method and obtained from 38 banks. By taking the research period for 2 years, namely in 2020 and 2021, 76 research data were obtained. Research data is obtained from the Otoritas Jasa Keuangan web and bank financial statements. Data analysis was performed using MRA using the SPSS Test tool Ver. 23. The results of the study showed that LDR had a negative effect on NPL. Asset Management can moderate that is, strengthen the relationship between LDR and NPL. The implications of the results of this study can be used by Rural Banks in taking policies related to the distribution of credit. Rural Banks remains cautious in determining the eligibility of prospective debtors to reduce NPL by applying the principles of creditworthiness.